Critical Point Theory Applied to a Class of the Systems of the Superquadratic Wave Equations. (5th January 2009) - Jung, Tacksun; Choi, Q-Heung
Abstract : We show the existence of a nontrivial solution for a class of the systems of the superquadratic nonlinear wave equations with Dirichlet boundary conditions and periodic conditions with a superquadratic nonlinear terms at infinity which have continuous derivatives. We approach the variational method and use the critical point theory which is the Linking Theorem for the strongly indefinite corresponding functional.